Characteristics and Functional Properties of Sorghum Protein (Kafirin) - Pereya Musigakun; Masubon Thongngam (Agriculture and Natural Resources, 2007)
Kafirin, the major sorghum storage protein, is alcohol-soluble protein. It is an alternative source for zein in the preparation of edible film. In this research, characteristics and properties of -kafirins from different sorghum cultivars were studied. They include yield and protein content of extraction, protein composition, microstructure, as well as color, water- and oil-binding capacity of protein concentrate. After extraction, 100 g of sorghum flour yielded 4.65-5.64 g of protein. The protein concentrate contained 77.48-83.13% protein. By using SDS-PAGE, the protein concentrate consisted of α-, β-, and γ-forms of kafirin. The results showed that α-kafirin had the highest proportion among groups. Protein bodies containing kafirin had spherical shape and hold tightly together. Moreover, the ones from KU 439 had larger size than those of KU 804. In addition, the color of sorghum protein concentrates from KU 804 was more yellowish and brighter than KU 439. Water- and oil- binding capacities were decreased with increasing protein concentration.